Impact of design parameters on oil recovery performance in polymer flooding with low-salinity water-flooding. Issue 2 (3rd March 2020) - Yoo, Hyunsang; Lee, Jeonghwan
ABSTRACT: This study investigates the impact of design parameters on oil recovery performance in polymer flooding (PF) with low-salinity water-flooding (LSWF). Convergence technology for enhanced oil recovery (EOR) has recently been drawing attention as an upcoming technology to evolve toward similar performance and synergies. As one of the convergence technologies, PF utilizing low-salinity water is applied to improve oil recovery. In this study, an attempt is made to identify its mechanisms and to understand the low-salinity effects on PF in complex oil fields. Injection scenarios are made up to identify the efficiency of combining LSWF and PF (LSWF-PF), and sensitivity analysis is performed on the design parameters, such as slug size, salt concentration, and polymer viscosity, which are considered to be the most influential parameters. The results indicate that the efficiency of PF is significantly improved by using low-salinity water as the polymer solvent and the slug size of low-salinity water should be preferentially considered for the successful application of LSWF-PF in high-salinity reservoirs. Therefore, it is believed that a criterion can be set up to decide the design parameters of LSWF-PF, which can improve synergy effects in EOR processes.